What determines the public's support for water quality regulations to mitigate agricultural runoff?. Issue 101 (November 2019) - Guo, Tian; Gill, Devin; Johengen, Thomas H.; Cardinale, Bradley L.
Highlights: Effectiveness of voluntary programs affect support for regulatory policies on nutrient runoff. A prior beliefs, risk perceptions, and trust affect policy support. Belief about regulation and accountability and trust in farmers are key predictors. Abstract: For many freshwater systems, mitigating agricultural runoff of nutrients is a key requirement for curbing eutrophication and reducing subsequent ecological threats. However, defining the best way to achieve reductions in agricultural runoff can be a contentious issue. A policy debate is currently unfolding in Ohio focused on whether the state government should introduce regulatory policies on agriculture to reduce nutrient loadings from watersheds in an attempt to also reduce harmful algal blooms in Lake Erie. To inform policy development, we used a survey instrument to gauge public acceptance of regulatory policies and examined the psychological determinants of Ohio residents' support for a regulatory policy proposal that would introduce fines on excessive agricultural runoff. We designed a survey instrument with nine predictors of people's willingness to support regulations: 1) effectiveness of voluntary programs, 2) risk perception, 3) water quality perception, 4) trust in farmers, 5) trust in state government, 6) belief about fertilizer runoff as a major cause of HABs, 7) belief that farmers alone should not bear the burden to restore water quality in Lake Erie, 8) belief that regulation is necessary to keep farmers accountable, and 9) belief that regulation harms economy and employment. We also measured variables that represented different levels of self-interests, awareness of reduction goals, political party affiliation, and demographic characteristics. We collected a sample of 1000 respondents, who were representative of Ohio residents by age, gender, race, and education level. Most predictors were significant and in the directions hypothesized, with exception of water quality perception and belief about regulation and jobs. One's a priori belief that regulations are necessary to keep farmers accountable for their land management practices had the largest enhancing effect for accepting a regulatory policy of fines, while trust for farmers had the largest inhibiting effect. In comparison, water quality perception was not significant in predicting individual policy attitudes. This study informs the public engagement and communication efforts and suggest directions for future research on public policy support.